Maternal Self-Confidence and Breastfeeding after Participating in a Program about Infant Prone Positioning. Issue 4 (July 2021) - Jesberger, Colleen; Chertok, Ilana Azulay; Wessells, Allyson; Schaumleffel, Carol
Abstract: Purpose: Maternal self-confidence facilitates infant growth and new mother role development. Infant ability to breastfeed and maternal breastfeeding self-confidence are imperative to helping mothers meet their breastfeeding goals. Consistent opportunity for infant movement in the prone position has been shown to improve breastfeeding ability; however, families report a lack of knowledge of how to safely support this activity. Perceptions of maternal self-confidence, infant development, and breastfeeding success upon completion of an infant prone positioning program with focus on posture, movement, and connection were studied. Study Design and Methods: Qualitative interviews were conducted among breastfeeding mothers in three states to explore maternal perceptions of learning about infant prone positioning. Results: Thirty-five mothers who completed an infant prone positioning program shared their perceptions of infant interaction, prone play and positioning, and breastfeeding self-confidence. Four primary themes were identified from the analysis: maternal knowledge and self-confidence; strategies and practices learned; breastfeeding benefits of infant prone positioning; and motivation for program participation . Clinical Implications: Our findings support consideration of teaching new mothers about prone positioning to enhance self-confidence in mothering, breastfeeding skills, infant development, and maternal–infant dyad bonding. Abstract : Infant prone positioning may be beneficial for breastfeeding. Women were interviewed after participating in a program about infant prone positioning to get their perceptions about the effects of learning infant prone positioning on maternal confidence and achieving their breastfeeding goals.